Avaliação bioeconômica de dietas para terminação de cordeiros mestiços deslanados no semiárido brasileiro - Santos, Francisco Naysson de Sousa (2018)
The objective of this study was to evaluate the reduction of protein and energy levels in diets for crossbred lambs wooless the Brazilian semiarid region in termination and its effects on intake and digestibility of nutrients, as well as on animal performance and economic evaluation. The experiment was conducted in laboratory Respirometry Embrapa Goats and Sheep. Twenty lambs from a commercial herd, with no defined racial pattern, four months old and body weight of 14.8 ± 3.52 kg were used. The experimental treatments consisted of a factorial design consisting of two dietary formulations for different maturity (early and late), according to NRC (2007) and two levels of these formulations reductions (0 to 10% reduction in Crude Protein and Total Digestive Nutrients values indicated by international system. There was higher consumption of fibrous fractions to animals fed diets to late maturity. There was an increase in dry matter intake for animals of late maturity, this increase may have been the animal strategy to meet the nutritional requirements of crude protein and total digestible nutrients. The values higher digestibility of dry matter observed for early maturity, can be related to higher energy levels in the diets. Regarding the nitrogen balance (%), it was positive for the levels of reduction and maturity, indicating that there was retention of protein in the animals' bodies. There was interaction effect (P <0.05) for the total weight gain and average daily weight gain. As expected, the average daily gain (ADG) showed correlation between the dry matter intake and metabolizable energy intake. Lie down with crude protein and energy reductions were those that had lower costs within the containment system. However, although there was an increase in the total costs, with power primarily to increased use of concentrate use, you can see that the productive response (increased production) offset the increase in costs in order to provide better economic results. Reductions in nutrient content to late maturity condition with a reduction of 15% was found to be an attractive situation, represented by the internal rate of return. Diets influence on intake and digestibility of nutrients for early maturity with a reduction of 0%, and late maturity with a reduction of 15% of CP and TDN requirements. The diet with a reduction of 15% for late maturity was the most attractive, because it presented lower cost with food and better net income